Investing for Profit: A Study of Iska up to the Time of Rabbi Abraham ben David of Posquieres - Gamoran, Hillel (Hebrew Union College annual, 1999)
Although lending on interest was forbidden, the Mishnah allowed investments for profit in which investors and managers shared the profits (or losses) from their business enterprises. The Talmud called an investment of this nature an iska and placed restrictions on the iska so that it would not result in the law against usury being broken. The Geonim and the early Rishonim maintained these restrictions in full force, but, in the twelfth century, Rabbi Abraham ben David of Posquieres (Rabad) took a different approach than did his predecessors. He interpreted the law in such a way as to ease the restrictions and encourage investment for profit. Rabad's liberal rulings may be explained by the increased commercial activities of his time and by pressure brought by the Jewish business community on the rabbinic authorities to reduce the burden imposed by the usury ban. It may also be explained by the personality of Rabad, an independent thinker, who did not hesitate to strike new paths in the law.